OPTIMALISASI STRATEGI BISNIS KOPERASI X DI BUKITTINGGI MELALUI DIGITAL MARKETING DAN PENGELOLAAN KEUANGAN YANG EFEKTIF - Pramadian, Budi; Sari, Laynita; Septiano, Renil (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study examines the business optimization strategy of Koperasi X in Bukittinggi through the utilization of digital marketing and effective financial management. Based on the Internal-External (IE) Matrix analysis, the cooperative is positioned in the "Maintain and Sustain" quadrant, with IFE and EFE scores of 2.72 and 2.70, indicating stable internal and external conditions, although efforts are still needed to improve its competitiveness and growth. The recommended strategies include market penetration and product development, which can be enhanced by implementing digital marketing to expand market reach and increase member engagement. Additionally, efficient financial management will ensure transparency, proper fund allocation, and the sustainability of cooperative operations. The combination of digital marketing and effective financial management will strengthen the cooperative's position, foster innovation, and support sustainable growth, enabling Koperasi X to maintain competitiveness and provide greater benefits to its members in the digital era